Bringing class back in: class consciousness and solidarity among Chinese migrant workers in Italy and the UK - Wu, Bin; Liu, Hong (Taylor & Francis, 2014)
The growing literature on international migration has a tendency to emphasize homogenous elements such as shared ethnic background, social network and cultural similarities in shaping immigrants' identity. We argue that this underestimates the differences (and sometimes conflicts) of interests between ethnic employers and migrant workers and that class needs to be brought back into the studies of ethnic relationship. Based upon findings from a series of fieldwork in Veneto, Italy and East Midlands, UK, this article contends that class consciousness has co-existed, sometimes uneasily, alongside co-ethnic and cultural relationships among Chinese migrant workers and has played an important part in the making of new Chinese communities. By analysing the perspectives of Chinese migrant workers and their relationship with co-ethnic entrepreneurs, this article illustrates complex factors behind the formation, diffusion and development of class consciousness among Chinese migrant workers.